Location-Based System for Food Crowdsourcing - Abobakr Ahmed, Mohammed Al-Sakkaf (Universiti Malaysia Sarawak (UNIMAS), 2019)
Food banks are responsible for food redistribution to people suffering from food insecurity within a certain area. They also contribute to raising the community’s awareness of food insecurity or poverty, thus encouraging every community member to be part of the solution. Food banks coordinate the surplus redistribution process where they may be involved in various activities such as managing, collecting, packaging, fundraising, and promotion. Hence, it consumes a lot of resources such as employees and volunteers in order to accomplish those tasks. However, there is no effective or efficient way in which the food redistribution process is automated. This situation leads to the public and businesses’ disengagement and discouragement in food donation, thus increasing food waste. As a result, this project aims to provide a web application to connect all parties or stakeholders involved in the food sharing process. The proposed system can facilitate the way the donations are made, processed, collected, and then claimed. It is based on the crowdsourcing concept enabling crowds to play an important role in the food distribution process. Donors are enabled to make food pickup requests and online fundraising. It also allows volunteers to participate and help in food collection and distribution. On the other hand, food banks will be able to manage and track all donations. The user acceptance testing conducted to get the feedback of the users by asking them to use the system and fill up the provided online questionnaire, which is designed to measure the level of acceptance of the system. Positive feedback from users are obtained.